Cáncer de próstata: rol actual de la ecografía transrectal y biopsia dirigida por ultrasonido. - Delgado, Gonzalo; Fernández A., Manuel (Revista Hospital Clínico Universidad de Chile, 1997)
Prostatic carcinoma: the use of transrectal ultrasound and sonographycally directed prostatic biopsyThe importance of latent carcinoma of the prostate, the significance of the palpable prostatic nodule, the progress and the clinical use of screening for carcinoma of the prostate with prostate specific antigens, the effect of digital rectal examination on prostate specific antigen and the diagnosis of prostatic carcinoma with the use of transrectal ultrasound and sonographycally directed prostatic biopsy are analized by the authors.